Analisis Faktor – Faktor yang Mempengaruhi Risiko Likuiditas - Dahrul Siregar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
Liquidity risk is the ability of a bank to fulfill a predetermined obligation at maturity. Measurement of liquidity risk can be seen in the short and long term through: DER, FDR, Inflation, NPF. The data used are secondary data based on observations of the liquidity risk of Islamic banks and conventional banks from 2007 to 2016. Data collection is also obtained from the Sharia Banking Statistics Report published by the Financial Services Authority and Bank Indonesia. Descriptive research methods and data analysis techniques using multiple regression analysis model) with the ECM (Error Correction Model) approach. Overall, both the short and long term DER variables on Liquidity Risk show a significant relationship, as well as the FDR variable on Liquidity Risk shows a significant relationship, the inflation variable on liquidity risk shows a significant relationship, the NPF variable on liquidity risk in the short term it shows no significant relationship, on the other hand, the NPF variable on liquidity risk in the long term shows a significant relationship